Unpaid overtime in Germany : differences between East and West - Silke Anger (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2003)
Although the standard work week is longer in East than in West Germany, there is a higher incidence and average amount of unpaid overtime worked in the new states. We try to explain the striking differences in unpaid overtime by analyzing the labor supply side. We focus on the investment character of overtime and examine whether workers use unpaid extra hours to signal higher productivity so as to reduce the risk of losing their job. Using panel data from the GSOEP we find partial evidence for our unemployment-overtime hypothesis.
urn:nbn:de:kobv:11-10050760
Keywords: J22; C23; D80; 330; unpaid overtime; labor supply; signaling; unemployment; panel data; Überstunden; Arbeitslosigkeit; Arbeitsproduktivität; Signalling; Schätzung; Alte Bundesländer; Neue Bundesländer; Deutschland